Continuing the Journey of Education, Training and Research - Koirala, Amit; Adhikari, Ekaraj (Journal of Training and Development, 2015)
DOI: http://dx.doi.org/10.3126/jtd.v1i0.13082 Journal of Training and Development Vol.1 2015: 1-2